Mutation analysis of SHP2, SOS1, and SOS2 related to dysregulation of Ras/MAPK pathway in Noonan syndrome - Nihayatul Karimah (Acta Biochimica Indonesiana, 2024)
Background: Noonan syndrome, characterized by short stature, congenital heart defects, and facial dysmorphology, results from dysregulation of the Ras/MAPK pathway. Mutations in Ras/MAPK pathway proteins such as SHP2, SOS1, and SOS2 are responsible for this condition. Objective: This study aimed to model the mutations in SHP2, SOS1, and SOS2 using FoldX and predict the structural impact. Methods: Mutations were sourced from the OMIM Database. Protein sequence was retrieved from UniProt, and evolutionary conservation profiles were estimated by ConSurf. The structures of SHP2 and SOS1 were obtained from Protein Data Bank, while the undefined structure of SOS2 was modeled using YASARA. FoldX was used to model the mutations in two steps: structure repair and residue mutation. Results: The evolutionary conservation profile indicated that most mutations occur in the highly conserved residues. These mutations disrupt various important interactions at domain interfaces. The total energy changes were predominantly positive, indicating instability in the mutated proteins due to the loss of the domain interactions and some unfavorable local conformational changes. Conclusion: FoldX is a valuable tool for modeling protein mutations and predicting altered function. The models demonstrate that the mutations contribute to the aberrant autoinhibitory control and catalytic activity of the proteins.